1999
DOI: 10.1007/s003300050694
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the breast in patients with metastatic disease of unknown primary

Abstract: The objective of this study was to assess the value of contrast-enhanced dynamic breast imaging in patients with carcinoma of unknown primary (CUP). Fourteen patients presenting with metastatic disease compatible with breast cancer (axillary lymph node metastasis: n = 6; supraclavicular lymph node metastasis: n = 1; bone metastasis: n = 3; liver metastasis: n = 3; lung metastasis: n = 1), who had no evidence of tumor in X-ray mammograms and ultrasound, underwent bilateral dynamic breast MR imaging. Suspicious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 10 publications
1
27
0
4
Order By: Relevance
“…Newer imaging techniques (Tilanus-Linthorst et al, 1997; Kole et al, 1998;Lenzi et al, 1998;Schorn et al, 1999;Stevens et al, 1999), such as breast MRI, positron emission tomography and other nuclear medicine techniques, that can give clues as to the site of the primary, presently remain of limited help.…”
Section: Discussionmentioning
confidence: 99%
“…Newer imaging techniques (Tilanus-Linthorst et al, 1997; Kole et al, 1998;Lenzi et al, 1998;Schorn et al, 1999;Stevens et al, 1999), such as breast MRI, positron emission tomography and other nuclear medicine techniques, that can give clues as to the site of the primary, presently remain of limited help.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of authors have confirmed the value of contrast-enhanced (CE) MRI for certain indications [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. However, accuracy data in the literature vary, and concern exists that a widespread use of CE MRI combined with insufficient standardization might cause costly work-up and unsatisfying results including false-positive and false-negative results.…”
Section: Introductionmentioning
confidence: 95%
“…In optical mammography, analysis of early and very early contrast enhancement is of interest for the following reasons: 1) Despite ongoing technical developments in MR imaging, the temporal resolution achieved is still lower than that of optical techniques [88,89]. 2) The contrast agent ICG differs from gadolinium-DTPA in terms of distribution in different compartments as ICG acts as blood-pool contrast due to strong protein binding ; this difference results from the strong protein binding of ICG, which makes ICG a bloodpool contrast agent [90].…”
Section: Indocyanine Green As An Contrast Agent To Enhance Absorptionmentioning
confidence: 99%